Effect of FES Limbs Cycling Training on Lower Limb Function and Walking Ability of Stroke Patients - Quansheng MA; Dejun SONG; Shuyan QI (康复学报)
Objective:To explore the effects of functional electrical stimulation (FES) limbs cycling training on lower limb function and walking ability of stroke patients.Methods:Forty-five stroke patients were assigned to FES limbs cycling training group (treatment group) and conventional rehabilitation training group (control group) by the random number table. Both groups received conventional clinical treatment and rehabilitation training. The treatment group was added with selective stimulation of lower limb muscles, and the intensity of stimulation was according to the tolerance of the subjects. The training lasted for eight weeks, five days a week, once a day and 20 minutes each time. The FES limbs cycling indexes, including the total distance of motion, the total power and the average electrical stimulation, the fugl-meyer assessment-lower extremity (FMA-L) and 10 m walking time (10mWT) of two groups were evaluated before and after the treatment.Results:After the treatment, the total distance of motor and total power of two groups were increased significantly (P<0.05), the average electrical stimulation was decreased significantly (P<0.05), and the increasing amplitude of total distance of motor in the treatment group was higher than that in the control group (P<0.05). After the treatment, the FMA-L score of two groups were increased significantly (P<0.05), and the increasing amplitude in the treatment group was higher than that in the control group (P<0.05). After the treatment, the 10mWT of two groups were decreased significantly (P<0.05), and the decreasing amplitude in the treatment group was higher than that in the control group (P<0.05).Conclusion:FES limbs cycling training could enhance the muscle function of lower limb and improve walking ability of stroke patients.